2019
DOI: 10.1002/ajoc.201900589
|View full text |Cite
|
Sign up to set email alerts
|

Selected Topics in the Syntheses of Bicyclo[1.1.1]Pentane (BCP) Analogues

Abstract: This Minireview focuses on selected topics in the syntheses of bicyclo[1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(34 citation statements)
references
References 119 publications
0
34
0
Order By: Relevance
“…[33] All the bi-or polycyclic ring systems shown in Figure 5 can be used as isosteres of monosubstituted and p- disubstituted benzene derivatives; in addition to that, they were proposed as analogues of tert-butyl group and internal alkyne moiety. The subject or its various aspects have been surveyed many times in recent years; [33,[392][393][394][395][396][397][398][399] the reader is referred to the cited reviews for detailed discussion of synthetic approaches, as well as applications in medicinal chemistry and other areas. If shortly, the isosteric replacements were typically aimed at increasing of the aqueous solubility and metabolic stability of the optimized compounds; this is especially true for the bicyclo [1.1.1]pentane (BCP) derivatives (Figure 6).…”
Section: Non-classical Sp 3 -Enriched Benzene Isosteres: An Escape From Flatlandmentioning
confidence: 99%
“…[33] All the bi-or polycyclic ring systems shown in Figure 5 can be used as isosteres of monosubstituted and p- disubstituted benzene derivatives; in addition to that, they were proposed as analogues of tert-butyl group and internal alkyne moiety. The subject or its various aspects have been surveyed many times in recent years; [33,[392][393][394][395][396][397][398][399] the reader is referred to the cited reviews for detailed discussion of synthetic approaches, as well as applications in medicinal chemistry and other areas. If shortly, the isosteric replacements were typically aimed at increasing of the aqueous solubility and metabolic stability of the optimized compounds; this is especially true for the bicyclo [1.1.1]pentane (BCP) derivatives (Figure 6).…”
Section: Non-classical Sp 3 -Enriched Benzene Isosteres: An Escape From Flatlandmentioning
confidence: 99%
“…Surprisingly, none of the works of Baran, Ma or Qin considers the synthesis of BCP derivatives containing bridge nitrogen substituents. This is in contrast to the considerable progress made towards installation of nitrogen atoms at the bridgehead positions, [17b, 69, 70, 77] for example, for bioisosteric replacement of anilines, common structural alerts and toxicophores in drug design. To date, nitrogen has only been installed on the bridge positions of BCP derivatives through Schmidt rearrangement of carboxylic acid 59 (Schemes 12 and 19) by Wiberg [35b] .…”
Section: Nitrogen Substituentsmentioning
confidence: 90%
“…SHELXT-2015; [51] structure refinement, SHELXL-2015. [52] 2-Cyano-1,1-difluoropropan-2-yl acetate (8). TMSCN (350 g, 3.53 mol) was added in portions to a mixture of 1,1-difluoroacetone (332 g, 3.53 mol) and Sc(OTf) 3 (8.68 g, 17.7 mmol) under 30 °C with external water cooling bath.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4] A number of saturated bicyclic bioisosteres were proposed to replace flattened aromatic rings such as benzene, bicyclo[1.1.1]pentane (BCP) being one of the most renown ones. [5][6][7][8][9][10][11][12][13][14][15] Recently, Mykhailiuk and co-workers proposed another closely related benzene isostere -2-oxabicyclo[2.1.1]hexane (Figure 1A). [16] It was shown that derivatives of this scaffold have improved aqueous solubility and hydrophilicity as compared to their benzene-and BCP-derived counterparts.…”
Section: Introductionmentioning
confidence: 99%